Strategi Guru dalam Menanamkan Nilai Kejujuran Melalui Pembelajaran Akidah Akhlak di Kelas IV MIN 3 Bangka - Viyola Romadona; Danang Dwi Basuki (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
This study aims to analyze teachers’ strategies in instilling honesty values through Aqidah Akhlak learning among fourth-grade students in Islamic elementary schools (Madrasah Ibtidaiyah). The research employed a descriptive qualitative approach with a case study design conducted in an MI setting. The participants consisted of the Aqidah Akhlak teacher, the fourth-grade homeroom teacher, and fourth-grade students. Data were collected through classroom observations, in-depth interviews, and documentation, and were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that the most effective strategies include teacher role modeling, habituation of honest speech, anti-cheating learning contracts, storytelling of Prophet Muhammad as Al-Amin, daily reflection, and students’ honesty journals. These strategies were integrated into lesson openings, group discussions, individual assignments, daily assessments, and informal interactions outside the classroom. The implementation significantly improved students’ willingness to admit mistakes, reduced cheating behavior, strengthened confidence in telling the truth, and increased peer trust. Supporting factors included teacher consistency, a religious school culture, and parental support, while peer influence and digital media exposure emerged as major challenges. The study highlights that the integration of role modeling and habituation within Aqidah Akhlak instruction is highly effective in fostering honesty as a foundational Islamic character from an early age.